Human herpes virus 6B and mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS): is there a link? - Leal, B. (2014)
Purpose: Human Herpesvirus 6 (HHV-6) is a ubiquitous virus acquired mainly during the first 2 years of life. Mesial Temporal Lobe Epilepsy with Hippocampal Sclerosis (MTLE-HS) is the most frequent pharmacoresistant epilepsy. One of the most common antecedents of MTLE-HS is febrile seizures (FS). Although the aetiology of MTLE-HS remains unclear, evidences suggest that HHV-6 infection could be implicated. The objective of this study was to investigate the presence of HHV-6B DNA in the hippocampus and adjoining temporal cortex of MTLE-HS patients submitted to surgery. Methods: A total of 22 MTLE-HS (13 females and nine males) cases were studied. The mean age at surgery was 39 9 years and mean age at onset of seizures was 10 6 years. These study cohort was compared to a group of 10 epileptic patients without MTLE-HS (six females, four males; mean age = 26 15 years) and with autopsy material from nine individuals without neurological disease. HHV-6B DNA was identified by real-time PCR with specific TaqMan probes. Results: We detected HHV-6B DNA in only one hippocampus from a MTLE-HS patient. This patient had a disease duration of 36 years and a history of febrile seizures in childhood. None of the non-MTLE or controls specimens showed positivity for HHV-6B. Conclusions: Our findings do not support a relevant etiologic role for HHV-6B in MTLE-HS, at least in this population. However, the possible role of viral infection in MTLE-HS epileptogenic process, in individual cases, cannot be excluded.